Limiting glucocorticoid secretion increases the anorexigenic property of Exendin-4 - Shin J. Lee; Katharina Diener; Sharon Kaufman; Jean-Philippe Krieger; Klaus G. Pettersen; Nino Jejelava; Myrtha Arnold; Alan G. Watts; Wolfgang Langhans (Molecular Metabolism, 2016)
Objective: Glucagon-like peptide-1 (GLP-1) analogs are attractive options for the treatment of type II diabetes and obesity because of their incretin and anorexigenic effects. Peripheral administration of the GLP-1R agonist Exendin-4 (Ex-4) also increases glucocorticoid secretion in rodents and humans, but whether the released glucocorticoids interact with Ex-4's anorexigenic effect remains unclear. Methods: To test this, we used two experimental approaches that suppress corticosterone secretion and then assessed Ex-4 effects on eating in adult male rats. First, we combined acute and chronic low dose dexamethasone treatment with Ex-4. Second, we ablated hindbrain catecholamine neurons projecting to the hypothalamus with anti-dopamine-β-hydroxylase-saporin (DSAP) to block Ex-4-induced corticosterone secretion. Results: Combining dexamethasone and Ex-4 produced a larger acute anorexigenic effect than Ex-4 alone. Likewise, chronic dexamethasone and Ex-4 co-treatment produced a synergistic effect on eating and greater body weight loss in diet-induced obese rats than Ex-4 alone. DSAP lesions not only blunted Ex-4's ability to increase corticosterone secretion, but potentiated the anorexigenic effect of Ex-4, indicating that Ex-4-dependent corticosterone secretion opposes Ex-4's actions. Consistent with the enhancement of Ex-4's anorexigenic effect, DSAP lesion altered Ex-4-dependent changes in neuropeptide Y, preproglucagon, and corticotropin releasing hormone gene expression involved in glucocorticoid feedback. Conclusions: Our findings demonstrate that limiting glucocorticoid secretion and actions with low dose dexamethasone or DSAP lesion increases Ex-4's ability to reduce food intake and body weight. Novel glucocorticoid receptor based mechanisms, therefore, may help enhance GLP-1-based obesity therapies. Author Video: Author Video Watch what authors say about their articles Keywords: GLP-1, Exendin-4, Corticosterone, Anti-dopamine-β-hydroxylase-saporin, Hypothalamus, Neuropeptide Y